Left ventricular function in Nigerian diabetics with or without hypertension (Tanzania Medical Journal, 2015)
Objectives: This study evaluated left ventricular function, using echocardiographic methods, in Nigerian diabetics with additional aim of assessing the effect of coexisting hypertension. Design: A descriptive cross sectional studySetting: Hospital based studySubjects: Ninety five subjects aged 30-60 years comprising 31 hypertensive diabetics, 30 normotensive diabetics, and 34 age- and sex- matched non diabetic non hypertensive subjects as control.Main Outcome measures: All subjects had transthoracic 2D/Mmode and Doppler flow echocardiography performed to determine left ventricular systolic and diastolic functions.Results: Age and sex of the subjects were comparable. Duration of diabetics for hypertensive diabetics and normotensive diabetics were 36.78 ±31.26 months and 36.12 ± 47.50 months respectively. Mean fasting blood glucose was significantly higher in the normotensive diabetics (8.94 ± 2.13 mmol/L) than hypertensive diabetics (6.04 ± 2.01 mmol/L); p=0.038. There was stepwise reduction in Left Ventricular Ejection Fraction(LVEF) from normal controls (71.77 ± 8.26 %) to normotensive diabetics (65.34 ± 9.75 %) and hypertensive diabetics (64.29 ±10.99 %); p= 0.005. The diabetic subjects had impaired LV diastolic function, as shown by their significantly longer Isovolumic relaxation time (IVRT) and deceleration time and lower transmitral E: A ratio compared with controls. No statistically significant difference existed in these indices of LV diastolic function between the normotensive and hypertensive diabetics, thoughhypertensive diabetics had higher LVMI than the normotensive diabetics.Conclusion: Left ventricular function is impaired in diabetics. This may be independent of coexisting hypertension, though presence of hypertension appears to worsen it.